The effectiveness of trauma-informed youth justice: a discussion and review - Day, Andrew; Malvaso, Catia; Boyd, Carolyn; Hawkins, Katherine; Pilkington, Rhiannon (Frontiers in Psychology, 2023)
Youth justice services around the world are under increasing pressure to find new and more effective ways of working with young people. One way forward is to implement a more compassionate approach to service delivery that embraces the idea of ‘trauma-informed practice’. And yet, substantial variation has been observed in how a trauma-informed approach has been defined and understood by practitioners, with idiosyncratic implementation evident across different systems and only limited evidence that this results in reductions in subsequent re-offending. In this paper we argue that the success of efforts to work in more trauma-informed ways cannot be judged using recidivism data alone and that there is a need to identify key indicators of the effectiveness of any trauma- informed approach. We present the case for implementing trauma-informed youth justice and outline key features of the approach. We then present a logic model that articulates key components and identifies short- and longer-term outcomes that can be measured to assess the overall performance of a service. The article concludes with a discussion of the current evidential status of trauma-informed youth justice, identifying areas of current strength and those where further work is needed to develop the evidence base, including the need to demonstrate the hypothesized association between short-term trauma-informed practice outcomes and the longer-term goal of preventing re-offending.